The Study of A Linear and Non-Linear Optical Property for PMMA Thin Films Doped with the Rhodamine B Laser Dye and Ag Nano Particles are Used in Medicine - Mithaq M. Mehdy Al- Sultani (Journal of Global Pharma Technology, 2017)
Four different mixtures of ( 10-3 mol/l Rhoda mine B laser dye , 0.1 gm PMMA and one of Ag nano particles weights ( 0.02 gm ,0.04 gm , 0.06 gm and 0.08 gm ) )   had been prepared using chloroform solvent .Four different thin films had been made from these mixtures  using drop casting method .The absorption   spectrums of  these thin films had been taken . The absorption spectral properties as (peak wave length, peak absorbance and frequency difference at half absorbance maximum) had been measured depending on the absorption spectrums for thin films. The non- linear optical properties as (Transmittance difference )  ,Non –linear phase shift    , Non-linear Refractive index  , Minimum normalized transmittance  and  Non-linear absorption coefficient ) were calculated according to normalized transmittance data obtained from Z—scan setup with closed and open aperture .The main conclusion is that the Ag nano particles causes a shift of  the absorption wavelengths  to longer wavelengths ( red shift ) , so this helps in choosing the medium and nano particles with appropriate excitation wavelengths .Keywords: Rhoda mine B laser dye, Ag nano particles, Linear, Non-linear, Properties.